2004
DOI: 10.1021/ie030533r
|View full text |Cite
|
Sign up to set email alerts
|

Recycle Effect Index:  A Measure to Aid in Control System Design for Recycle Processes

Abstract: Systems with material and/or energy recycles are quite common in the chemical industry. Modeling and DCS-level controller design are quite challenging for such processes because separation of the overall process response into a direct (forward-path) response and an indirect (recycle-path) response is often difficult. Even when this is possible, one needs to know whether a feedback-only control structure is sufficient or an advanced control structure that employs a recycle compensator is necessary. Using contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Material and energy recycle affects process performance leading to complex dynamic behavior, such as inverse response, open loop instability and chaotic behavior. Several authors propose different strategies to quantify these effects (Denn and Lavie, 1982;Morud and Skogestad, 1994;MacAvoy andMiller, 1999, Jacobsen, 1997;Dimian et al, 1997;Semino and Giuliani, 1997;Bildea and Dimian, 2003;Lakshminarayanan et al, 2004;Bildea et al, 2004).…”
Section: Process-oriented Methods Systems With Recyclesmentioning
confidence: 99%
“…Material and energy recycle affects process performance leading to complex dynamic behavior, such as inverse response, open loop instability and chaotic behavior. Several authors propose different strategies to quantify these effects (Denn and Lavie, 1982;Morud and Skogestad, 1994;MacAvoy andMiller, 1999, Jacobsen, 1997;Dimian et al, 1997;Semino and Giuliani, 1997;Bildea and Dimian, 2003;Lakshminarayanan et al, 2004;Bildea et al, 2004).…”
Section: Process-oriented Methods Systems With Recyclesmentioning
confidence: 99%
“…For instance, Luyben 3 has shown that the poles of the transfer functions are changed with K r . More recently, Lakshminararayanan et al 13 have shown that the "recycle effect index", a measure of the recycle effect, was directly related to the product of K r and K p .…”
Section: Steady-statementioning
confidence: 99%
“…Intuitively, integration creates physical connections between process units that are not part of the main flux and can thus give rise to feedback interactions which increase the complexity of the dynamic behavior of the process. These effects (including inverse response and open-loop instabilities) are by now well-documented in the literature [2][3][4][5][6] and make the control of integrated process systems especially challenging. Furthermore, in the recent past, market conditions have become increasingly dynamic, dictating that the control of integrated chemical processes go beyond simple regulation at a steady state, and towards efficient transient operation within a broader operating envelope.…”
Section: Introductionmentioning
confidence: 99%